(untitled) (Carte Romanze, 2024)
The European Ars Nova project aims to produce a critical edition of just over 1000 Italian, French, and Latin texts set to music, dating between the 14th and 15th centuries. In the first part, the article analyzes the characteristics of the tradition of this repertoire, marked by witnesses with and without musical settings and by a distinctive relationship between the authorship of the composer and that of the author of the text. In the second part, the general editorial criteria adopted in the project are illustrated.